Implementation of Child-Friendly Justice Principles in the Criminal Justice System: Preventing Secondary Victimization among Child Victims of Violence - Anggreany Haryani Putri; Endang Hadrian; Trias Saputra (Greenation International Journal of Law and Social Sciences, 2026)
Child victims of violence involved in the criminal justice system are vulnerable to secondary victimization due to various legal procedures that may cause psychological distress and retraumatization. This condition highlights the importance of implementing child-friendly justice principles as a means of safeguarding children throughout legal proceedings. This study aims to analyze the implementation of child-friendly justice principles within the Indonesian criminal justice system and to identify their contribution to preventing secondary victimization among child victims of violence. This study contributes to the literature by examining child-friendly justice as a preventive framework against secondary victimization and by linking international child protection standards with the Indonesian criminal justice system. The research employs a normative legal research method using statutory and conceptual approaches. Research data were collected through library research, encompassing legislation, international legal instruments, scholarly literature, and relevant previous studies. Data were analyzed qualitatively through interpretation, comparison, and evaluation of legal provisions and concepts related to child protection. The findings indicate that child-friendly justice principles have been incorporated into various national regulations; however, their implementation continues to face challenges, including limited child-friendly facilities, inadequate professional competence among law enforcement officials, and insufficient support services. The application of child-friendly interview rooms, single-interview procedures, psychological assistance, identity protection, and the involvement of trained personnel has been shown to contribute to reducing the risk of secondary victimization. Therefore, strengthening the implementation of child-friendly justice principles is essential to establishing a criminal justice system that is more responsive to the protection and recovery of child victims of violence.